Interleukin-15 in gene therapy of cancer - Ochoa, Maria C. (2013)
Interleukin-15 (IL-15) exerts powerful stimulatory effects on lymphocyte subsets that result in antiviral and antitumoral activities. The functions of this cytokine are mainly mediated in a cell-to-cell contact fashion termed IL-15 trans-presentation. This function is mediated by a cell which tethers IL-15 to its plasmatic membrane complexed to IL-15 receptor alpha (IL-15Rá). Such surface complexes interact with interleukin-2 receptor beta and gamma on the adjacent cell to elicit signaling. Unlike interleukin-2, IL-15 protects from activation-induced cell death and does not promote regulatory cells. These features underlie its activity against transplanted tumors and its adjuvanticity in tumor and viral vaccines. The GMP-manufactured recombinant protein is undergoing clinical trials but its rapid renal clearance calls for biotechnological strategies to increase molecular weight and ensure IL-15Rá. trans-presentation. Since early efforts with stable transfected tumor cells, IL-15 has been tested in a variety gene therapy approaches. Those mainly include transfer of expression cassettes to tumor cells, T cells, dendritic cells, vaccination sites and the liver as a biofactory organ. Detailed mechanistic knowledge of IL-15 biology is envisaged to make the most of a powerful immunotherapeutic tool ranked as one of the most promising for cancer immunotherapy.